2020
DOI: 10.1016/j.joule.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Thermal Runaway of Lithium-Ion Batteries

Abstract: This paper summarizes the mitigation strategies for the thermal runaway of lithium-ion batteries. The mitigation strategies function at the material level, cell level, and system level. A time-sequence map with states and flows that describe the evolution of the physical and/or chemical processes has been proposed to interpret the mechanisms, both at the cell level and at the system level. At the cell level, the time-sequence map helps clarify the relationship between thermal runaway and fire. At the system le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
434
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(438 citation statements)
references
References 76 publications
2
434
0
2
Order By: Relevance
“…Most of the thermal runaway is triggered by the reaction derived from electrodes. [ 6 ] The decomposition of cathode materials releases heat and oxygen and will trigger the combustion of flammable organic electrolytes. However, the high‐energy cathode is essential for an energy‐dense battery.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the thermal runaway is triggered by the reaction derived from electrodes. [ 6 ] The decomposition of cathode materials releases heat and oxygen and will trigger the combustion of flammable organic electrolytes. However, the high‐energy cathode is essential for an energy‐dense battery.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reveals that another abuse condition should be considered where the batteries are working above their capability (e.g., extreme fast or slow charging, ultrahigh operation temperature). [ 2 ] This is known as electrochemical abuse ( Figure 6 a). It occurs when the electrochemical device is forced to function beyond its capacity in electrochemical power outputs.…”
Section: Mechanism Of Trmentioning
confidence: 99%
“…a) Schematic of connection between the various abuse conditions for a battery TR and (b) the reactions and mitigation strategies of a battery TR during the abuse conditions at material, cell, pack, module, and vehicle levels (E, electrical abuse; M, mechanical abuse; TH, thermal abuse). [ 2 ] Reproduced with permission. [ 2 ] Copyright 2020, Elsevier.…”
Section: Mechanism Of Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, the thermal runaway mechanism of LIBs is demonstrated to be associated with a series of exothermic chain reactions, including decomposition of solid electrolyte interface (SEI) layer, anode/electrolyte reactions, self-decomposition of electrolyte, and cathode/electrolyte reactions, etc. [21][22][23][24][25] However, very recently, Prof. M. Ouyang et al revealed that the oxygen released from nickel-manganesecobalt (NMC) cathode will be consumed by the lithiated anode with great heat generation, triggering the thermal runaway of LIBs. 10 Differently, by analyzing the released gas, N. E. Galushkin et al propose that the powerful exothermic reaction from recombination of atomic hydrogen accumulated at anode graphite will contribute to the initiation of thermal runaway of LIBs.…”
Section: Introductionmentioning
confidence: 99%